2020
DOI: 10.37871/jbres1175
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Remdesivir: How to Improve for COVID-19 Treatment

Abstract: Potential clinical benefit in SARS-CoV-2 infection upon remdesivir treatment has been established. Recently, FDA has granted full approval for the clinical use of remdesivir for COVID therapy. However, the efficacy of remdesivir alone or in combination with other antivirals is still open to research, especially in terms of benefits vs. risk ratio. We here review remdesivir therapy based on a search for relevant pharmacological evidences with regards to the Pharmacokinetics (PK) and Pharmacodynamics (PD) of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The antiviral efficacy and potency and the cytotoxicity of the antiviral compound NV-CoV-2 in cell cultures were studied (Li et al, 2007;Barton et al, 2011Barton et al, , 2016Chakraborty and Diwan 2020a;Chakraborty and Diwan 2020b;Diwan et al, 2021b). Relative CPE levels were compared between all groups to identify any reduction in viral replication, as a reduction in CPE compared to untreated infected controls suggests a decrease in virus production/growth/spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral efficacy and potency and the cytotoxicity of the antiviral compound NV-CoV-2 in cell cultures were studied (Li et al, 2007;Barton et al, 2011Barton et al, , 2016Chakraborty and Diwan 2020a;Chakraborty and Diwan 2020b;Diwan et al, 2021b). Relative CPE levels were compared between all groups to identify any reduction in viral replication, as a reduction in CPE compared to untreated infected controls suggests a decrease in virus production/growth/spread.…”
Section: Discussionmentioning
confidence: 99%
“…Proof-of-concept studies were conducted in CoV-NL63-infected cell in cultures and also in virus-infected rats (Chakraborty and Diwan 2020a;2020b) as the SARS-CoV-2 and CoV-NL63 bind to the same receptor, angiotensin-converting enzyme 2 (ACE2), for entry into the host cells (Li et al, 2007). With several studies, both in vitro and in vivo, we have shown that encapsulation of RDV in NV-CoV-2 and the stability of RDV as well as its overall antiviral efficacy of the proposed regimen has improved a lot (Chakraborty and Diwan 2020a;2020b).…”
Section: Nanoviricide Can Work As a Safe Cargomentioning
confidence: 99%